Adenosine Deaminase Activity in Serum of Diabetics: A Reflection of Glycemic Profile? - Poddar, Anirban; De, Devyani (International Journal of Applied Biology, 2023)
Diabetes presents with a constellation of symptoms,hyperglycemia being just one of them.The primary challenge faced by physicians is to achieve a control over this exorbitant blood sugar levels.Oral antidiabetic agents & insulin therapy are the primary modalities of treatment available presently. The most reliable diagnostic as well as prognostic marker used for this purpose is HbA1c. Adenosine Deaminase (ADA), an enzyme associated with purine metabolism is known to exert potent metabolic effects through its receptors. ADA is primarily an established inflammatory marker reflecting T lymphocyte activity .Adenosine,the substrate of ADA is known to affect cholesterol synthesis in liver,thereby serving as a key hinge in the fine balance between glucose & lipid homeostasis. Due to the association of ADA with glucose & lipid homeostasis ,the authors believe that studying ADA activity in serum of diabetics can reveal many important facts which might open a new dimension in diagnosis & treatment protocol for diabetes mellitus.The purpose of our study was to monitor ADA activity in serum of diabetic patients who are on oral antidiabetic drugs & do not have evidence of microvascular or macrovascular complications of diabetes & also determine if any correlation exists between fasting blood glucose,HbA1c & serum ADA activity.